Factor Analysis of Expectancy, Value, and Sensitivity to Delay - Endy; Siaputra, Ide Bagus (ANIMA Indonesian Psychological Journal, 2012)
One of the way to gather information on procrastination is using a specific measuring instrument/ scale based on a theoretical construct and which is able to explain procrastination compre-hensively. Thus, the scale can be used as a predictor of procrastination. Unfortunately, that kind of scale is still limited. This study aims to validate the scale that can be a predictor of procrastination, namely Temporal Motivational Test (TMt), which is based on Temporal Motivational Theory (TMT), a theoretical construct that can explain procrastination comprehensively. In this study, validity of scale obtained from correlating each component in this scale with valid procrastination scales. The results show significant correlation between each component of TMT and valid procrastination scales (r > .3 and p < .005). The second way is to test the internal structure. The result is, two of the three components of the scale is measuring the same thing, namely persistence. Salah satu cara mengumpulkan informasi tentang prokrastinasi adalah menggunakan instrumen/ alat yang berdasarkan konstruk teoretis yang mampu menjelaskan prokrastinasi secara terpadu. Dengan demikian skala itu dapat dipakai sebagai prediktor prokrastinasi. Sayang sekali skala demikian masih langka. Studi ini memvalidasi skala yang mampu memprediksi prokrastinasi, yaitu Temporal Motivational Test (TMt), yang didasarkan pada Temporal Motivational Theory (TMT), sebuah konstruk teoretis yang dapat menjelaskan prokrastinasi secara terpadu. Dalam studi ini, validitas skala diperoleh dari mengorelasikan tiap komponen dalam skala ini dengan skala prokrastinasi yang valid. Hasil menunjukkan korelasi yang bermakna antara tiap komponen TMt dan skala prokrastinasi yang valid (r > .3 dan p < .005). Cara kedua adalah menguji struktur internalnya. Hasilnya menunjukkan, dua dari tiga komponen skala ini mengukur hal yang sama, yaitu ketekunan.